The Duration of Menstrual Blood Loss: Historical to Current Understanding - Marwan Habiba; Giuseppe Benagiano (Reproductive Medicine, 2023)
Most published research focuses on the amount of menstrual blood loss and, to a lesser extent, on cyclicity. Little attention has been paid to the duration of bleeding, the factors that enable its cessation within a ‘normal’ timeframe, or to patterns that entail interruption and resumption of blood loss. The definition of what constitutes normal remains arbitrary and there is no therapy specifically designed to shorten the duration of bleeding. Here, we critically review the literature that addresses the duration of bleeding and the factors that trigger endometrial breakdown and repair. Available reports used population averages which mask inter- and intra-individual variations. The duration of bleeding is not necessarily linked to the amount of loss but may be influenced by age, ethnicity, habitus, region and altitude of residence, dieting and stress. The onset of bleeding has been linked to declining steroid production by the corpus luteum. There remains considerable controversy around the extent of endometrial shedding at menstruation. This is likely to vary within and between women. The significance of a change from previous patterns, very short or prolonged bleeding, days of light loss or spotting before or after days of bleeding, or of bleed-free days that punctuate flow, remain poorly understood.